Preliminary assessment on pretreatment methods for landfill waste utilization in biohydrogen production - Nur Sofiya Mohd Fauzi,; Nurul ‘Azyyati Sabri,; Mohd Fazli Farida Asras,; Hajar Fauzan Ahmad,; Nazira Mahmud, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Landfill waste consists of a mixture of components that have high potential as a substrate for hosting various microorganisms’ growth. Utilizing this waste as a fermentation substrate is seen as an economical solution for the management of the waste. Treating this waste is crucial to remove unnecessary components for the growth of specific organisms to ensure a high reaction yield. Fermentative hydrogen production from this waste specifically requires the hydrogen-consuming bacteria to be reduced. In this work, heat, ultraviolet (UV) radiation, acid, and alkaline pretreatment were conducted on the landfill waste. The changes in the reduced sugar content and appearance of bacterial colonies were observed and compared. Heat pretreatment at 65 °C was found to give among the best increase (74 – 88%) in reducing sugar content and reduction (50 – 85%) in the number of aerobic bacterial colonies detected. Global warming potential and eutrophication potential recorded from simulated heat pretreatment plant was comparable to other heat-based pretreatment reported by other researchers with a potential reduction in severity as the plant size increased.